MEMBANGUN KEPEMIMPINAN KUAT DAN TANGGUH PADA PENGEMBANGAN SUMBER DAYA APARATUR PEMERINTAH DAERAH MELALUI PENDIDIKAN DAN PELATIHAN - Edwin Wakak Megow; R. Widodo Triputro; Ardian Infantono (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
In the case of the economic recession of Covid-19 Pandemic nowadays, strong and resilient leadership in the dynamics of advances in Science Technology and Science (IPTEKS) and technology is always expected by the community, especially to support the goal of increasing the quality of national development in the area of Information and Communication (ICT) today. Leadership Resources of local government apparatus in Indonesia need to be developed using education and training methods. This research uses the descriptive-analytic method and implemented a literature study. The implementation of leadership tasks in the regions in the future is faced with several main issues that influence each other, namely science and technology as a concept of developing development forces faced with the dynamics of national, regional, and global. Theories that are considered relevant to be applied in the development of Regional Leaders Others are Behavioral Theory and Participative Theory. The research results discuss the Regional Heads and the Competencies of Leadership and Educational Personnel of the Institute for Regional Leadership Development. The Ki Hadjar Dewantara Leadership Trilogy, which has been implemented nationally until now, can be used as a permanent leadership development method in the regions. This research recommends a leadership development approach through three aspects, namely, the Aspects of Regional Leadership Development, Aspects of Increasing the Competence of Educational Personnel of the Leadership Training Institute, and the Aspects of Facilities. and Infrastructure.